British Power and International Relations during the 1950s : a Tenable Position? - Turner, Michael J. (Lexington Books, A division of Rowman and Littlefield Publishers, Incorporated, 2009)
This is an integrated international history that pays special attention to Britain's role and status. It contributes to the ongoing debate about Britain's 'decline' as a great power, and suggests that despite some retreats and compromises, Britain managed successfully to maintain its influence and defend essential national interests.